Indonesia’s Efforts in Law Enforcement for Transgressors of Indonesia - Malaysia Borders in Nunukan Regency - Mursit Mursit (Department of Political Science - Universitas Sains Al-Qur’an, 2021)
The government of Indonesia's efforts to reduce violations and enforce public law in Nunukan Regency, which is the border area or border between Indonesia and Malaysia, continue to be improved and maximized. Problems related to the situation and conditions in border areas include illegal cross-border activities and limited infrastructure. The writing method used is qualitative by expanding and sharpening the analysis combined with the experience (empirical) of the author who has served as a Legal Officer in the 614th Infantry Battalion/Raja Panditiha Task Force to guard Indonesia's land border with Malaysia in Nunukan Regency by discussing in detail related to border problems or social phenomena that exist and occur at the border. In its implementation in law enforcement efforts by the government at the border against border violators many are influenced by several factors including law enforcement, regulations that are not widely understood by the community, culture and local wisdom, as well as infrastructure and facilities for law enforcement itself. The central government needs to rebuild policies through a constructivist approach to be more progressive and focused in taking concrete actions to overcome and resolve the problem of lawlessness on the border in the Borneo Island.